Evaluation of Public Services through the "Lapor Pak Yes" Program at the Communication and Informatics Office of Lamongan Regency - Suwoto; Ika Devy Pramudiana; Sri Kamariyah; Zainal Fatah (International Journal of Scientific Multidisciplinary Research, 2024)
This study aims to evaluate the implementation of the "Lapor Pak Yes" program initiated by the Communication and Information Technology Office of Lamongan Regency as an innovation in public service. The program is designed to accelerate the resolution of public complaints through various communication channels, such as WhatsApp, Instagram, Telegram, and the national platform SP4N-LAPOR!. This research utilizes Dunn's (2003) policy evaluation theory, which includes six main criteria: effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness. A qualitative approach was employed in this study, with data collection techniques including in-depth interviews, observations, and document analysis. The study involves various stakeholders, including local government officials and community members who actively use the "Lapor Pak Yes" program. The data collected highlights findings regarding the program's effectiveness in addressing public complaints, the challenges faced, and its impact on improving the quality of public services. The findings reveal that although the number of complaints received was relatively high, with approximately 319 reports related to civil services in 2022, the rate of complaint resolution remains low. Around 40% of reports concerning infrastructure issues, such as road repairs and flood management, were not promptly addressed